GAYA HIDUP MODERN DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN KAIZEN HARITAGE COFFEE SHOP DI BEKASI - Nanda Sephia Delia; Fakhruddin Kurnia M (PIRSAP (Paser Institute for Scientific Research and Publications), 2025)
This study aims to measure the influence of modern lifestyle on purchasing decisions of consumers at Kaizen Heritage Coffee Shop in Bekasi. Businesses can also monitor social media trends and use them to their advantage in attracting customer attention and influencing purchasing decisions. This is a qualitative research study. The results of this study indicate that the variable of modern lifestyle has a positive influence on purchasing decisions at the coffee shop. This study recommends that Kaizen Heritage Coffee Shop in Bekasi should wisely enhance the influence of modern lifestyle. The limitation of this research lies in the research object, which was only conducted at Kaizen Heritage Coffee Shop in Bekasi. This can be a suggestion for future researchers. This study integrates the variables of modern lifestyle and purchasing decisions into a single research model conducted at Kaizen Heritage Coffee Shop in Bekasi. The objective of this research is to analyze the influence of modern lifestyle on consumer purchasing decisions at Kaizen Heritage Coffee Shop in Bekasi. By understanding the relationship between these two variables, this study is expected to provide strategic input for business owners in designing marketing approaches that align with the characteristics and preferences of today's consumers.